Spearfishing as a potential threat to fishery sustainability in Jamaica: a survey of 23 fishing beaches - Ennis, Zahra (2014)
Spearfishing was becoming an increasingly important economic activity in the Caribbean as a result of socioeconomic factors related to underemployment and the low capital outlay for equipment. For a year (2011) we surveyed spearfishing in 23 Jamaican beaches. Spearfishing has expanded from approximately 1% of fishers in 1991 to about 10% in 2011. The fishery is larger than expected and probably produced 4 000tons per year. Though reef fishes dominated catches, other resources such as lobsters, conch and octopus were regularly taken. Many small juvenile fishes were observed in catches well below their adult or optimum sizes. A total of 58% of spear-fishers reported they would have significant difficulty findingalternative employment if spearfishing was banned. Spearfishers reported exploiting the entire island shelf and also nearly all the offshore banks, especially Pedro Bank. Night spearfishing was common and targeted sleeping reef fishes. The activity is banned and should be enforced. Our recommendations include: register all spearfishers, actively manage spearfishing, apartial ban for part of the year and a ban on using scuba and hookah gear for spearfishing. Rev. Biol. Trop. 62 (Suppl. 3): 141-149. Epub 2014 September 01.